The Effects of Singaporean Math Model Method in Learning Place Values in Mathematical Operations - Gizella Ann Dumdum; Princess Kate Sagarino; Jeymarie Sanchez; Jovenil Bacatan (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2022)
The study was conducted to determine if the utilization of Singaporean Math Model Method in learning place value in mathematical operations has an impact to the improvement of students’ performance. A quantitative design was used in the study. The essential data were gathered from a total number of 67 respondents, 34 students from the experimental group and 33 students from the control group, with the aid of validated questionnaire. Data were analyzed and interpreted using the Average Weighted Mean and T-test as statistical tools. According to the findings of the study, data revealed that the result of pre-test and post-test of both experimental and control group is significant. Result showed that there is a significant difference of the utilization of Singaporean Math Model Method in learning Place Values in Mathematical Operations in Grade 3 Pupils at Kaputian Central Elementary School. Recommendations were also included in this study.